Market morality versus food safety: an approach from common good ethics - Lara Cortés, Claudio (Acta Bioethica, 2001)
Famine persistence around the world, despite its insufficient visibility in the media, makes it urgent to restate the issue of food safety. Nowadays economical policy models and warfare constitute clearly determinant factors in hanger, much more than natural disasters and farming production decreasing, formerly invoked. It is also clear that it is impossible to explain hanger in terms of food scarcity in the world. Nevertheless, these certainties do not produce coherent acting and policies since neo-liberal logic prevents the State to interfere with market rules. Along with the issue of hanger the dependence of many Latin American countries with regard to food supply becomes stronger, so producing a real food uncertainty. In this context it would be wise to consider the problem of food safety as an ethical issue within the perspective of common good in order to react adequately and timely.